VARIATION OF BODY SIZE AND WEIGHT OF MALE BALI CATTLE AGE 8 MONTHS IN THE BALAI PEMBIBITAN TERNAK UNGGUL DAN HIJAUAN PAKAN TERNAK DENPASAR - D. R., Puspitasari; Ardika, I N.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2018)
The activity was aimed to determine variation body size and body weight of bali calves in Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak Denpasar. BPTU-HPT Denpasar was one of the implementation of the Job Training Students of Faculty Animal Husbandry, Udayana University 2016. The object of this activity was bali calf 8 age months. Variable were includes the bali calf width at the body weight, chest circumference, body length, and height shoulder. The method used the direct internship and analyze of data recording from BPTU-HPT Denpasar. Data descriptive method by using simple statistical analysis to calculate the average of body size and body weight as well as the coefficient of variability. The results showed that average of body weight, chest circumference, body length, and height are respectively 89.4 kg; 105.9 cm; 78.8 cm; and 84.7 cm. The variation in body size length body and shoulder height above 10% while in chest circumference below 10%. Keywords: Diversity, Body Size, Body Weight, Recording, Bali Cattle Calf Males